2008
DOI: 10.1002/jcc.20943
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of densities for solid energetic molecules with molecular surface electrostatic potentials

Abstract: The densities of high energetic molecules in the solid state were calculated with a simplified scheme based on molecular surface electrostatic potentials (MSEP). The MSEP scheme for density estimation, originally developed by Politzer et al., was further modified to calculate electrostatic potential on a simpler van der Waals surface. Forty-one energetic molecules containing at least one nitro group were selected from among a variety of molecular types and density values, and were used to test the suitability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(34 citation statements)
references
References 24 publications
0
34
0
Order By: Relevance
“…The higher densities of tetrazole-N-oxides are presumably due to the intramolecular hydrogen bonds as well as the layered structures in the crystal lattice. Nevertheless, the absolute error in the calculated densities of designed compounds are expected to be less than 0.03 g/cm 3 and thus known to be fairly good to calculate performance properties [36][37][38][39][40][41].…”
Section: Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…The higher densities of tetrazole-N-oxides are presumably due to the intramolecular hydrogen bonds as well as the layered structures in the crystal lattice. Nevertheless, the absolute error in the calculated densities of designed compounds are expected to be less than 0.03 g/cm 3 and thus known to be fairly good to calculate performance properties [36][37][38][39][40][41].…”
Section: Densitymentioning
confidence: 99%
“…However, the detonation pressure varies with the square of density, when the density is greater than one. Several researchers have attempted to predict the densities with satisfactory accuracy [37][38][39][40][41].…”
Section: Densitymentioning
confidence: 99%
“…Since reliable prediction of density of an energetic compound is the utmost important for estimation of its performance, different approaches were developed to predict densities of energetic compounds, which have been reviewed elsewhere [14,15]. Quantum mechanical calculations require high-speed computer to conduct complicated calculations, which can be used for energetic molecules with simple molecular structures [16][17][18][19][20]. Among different quantum mechanical methods, Qiu et al [17] introduced a very direct approach to estimate the crystal densities of nitramines on the basis of the ratio of the molecular mass, in g/molecule, and the volume of the isolated gas phase molecule, in cm 3 /molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Kim et al have suggested that a prediction that differs by less than 0.03 g/cm 3 from the experimental value should be defined as 'excellent', while one that is between 0.03 and 0.05 g/cm 3 in error is still 'informative' [12]. For estimating the crystal density of available energetic materials, various methods have been developed.…”
Section: Introductionmentioning
confidence: 99%
“…For estimating the crystal density of available energetic materials, various methods have been developed. These include electrostatic potentials using quantum-mechanically determined molecular volumes [11][12][13][14][15], group additivities [8,9,[16][17][18], empirical methods [19][20][21][22] and Quantitative Structure-Property Relationships (QSPR) [23].…”
Section: Introductionmentioning
confidence: 99%